KOMODIFIKASI TUBUH PEREMPUAN DALAM IKLAN SMARTWATCH: KAJIAN ANTROPOLOGI KRITIS - Khoirunnisa Khoirunnisa (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
Smartwatch advertisements not only function as a medium for promoting technology but also as a space for the production of meanings regarding the body, health, and femininity in contemporary consumer culture. The female body in advertisements is often represented as a symbol of ideal health, productivity, and measurable self-control. This article aims to analyze the practice of commodifying the female body in smartwatch advertisements through a critical anthropological perspective within the framework of power relations and body normalization. This research uses a qualitative approach with visual analysis and critical discourse analysis methods on several advertisements that feature women as the main models. The results show that the female body is not only constructed as a visual object, but also as a moral object that is monitored, measured, and optimized through wearable technology. Smartwatches are positioned as devices that produce gender power relations through visual representations and narratives of health morality. These advertisements normalize ideal body standards while constructing health as a commodity that can be achieved through technology consumption, thus making the female body a primary arena for the operation of capitalism and power.